BENEFITS AND RISKS OF CHILDREN AND ADOLESCENTS USING SOCIAL MEDIA - Tartari, Elda (European Scientific Journal, ESJ, 2015)
Children and teenagers widely use social media, and recent studies have shown that they spend majority of their time daily in social media pages. This study aims to show the positive and negative impacts that social media has in the development of the teenagers. This review brings together work from disparate fields which examine the relationship between social media and social capital, privacy, youth safety, psychological well-being, and educational achievement. We observed this phenomenon in Albania by interviewing teenagers between 11-16 years of age. Those selected were regular users of social media. The study shows that children and teenagers were positively affected as social media helped in increasing their communication abilities, getting information, developing their technical skills, and how they can effectively use this recent technology. On the other side, they are exposed to risk of Facebook depression, cyberbullying, and online sexual harassments. In the conclusions part of this study, some suggestions were given for further studies.